Konflik di Era Otonomi Daerah - ROBINSON SEMBIRING (Universitas Sumatera Utara, 2011)
Base on National Report Goverment Decentralization Survey 2002 by Centre for Population and Policy Studies Universitas Gajah Mada (UGM) with PEG USAID-UNDP World Bank, have fund interesting of data about conflict in North Sumatera Province. The first in nation trial case, North Sumatera province is more peace from conflict if compared to Riau Province. Second, in national case, North Sumatera province is one that can provide conflict resolution to maintain harmonism. This research answer why this phenomenon happened and observes what is conflict potency in North Sumatera Province related to regional autonomy era. It is so interesting be-cause in the past North Sumatera Province often estimated as a gristle area. To be parallel with the society has hard character, heterogeneous and very dinamic. This study has found that in North Sumatera people standing in “conflict potencial” category. In this research appertain as lowest category. Because of that dynamics and violence of North Sumatera society basically is invisible.Keywords: Regional autonomy, social-political relationship, social conflict.